Hamiltonian formulation of anomaly free chiral bosons - Abdalla, E.; Abdalla, M. C B [UNESP]; Devecchi, F. P. [UNESP]; Zadra, A. [UNESP] (Elsevier B.V., 1988)
Starting out with an anomaly free lagrangian formulation for chiral scalars, which includes a Wess-Zumino term (to cancel the anomaly), we formulate the corresponding hamiltonian problem. Then we use the (quantum) Siegel invariance to choose a particular solution, which turns out to coincide with the one obtained by Floreanini and Jackiw. © 1988.